إشكالية النزعة الإيديولوجية في أدبيات التنمية السياسية - زبيري, رمضان (جامعة الوادي University of Eloued, 2019)
تناقش هذه الدراسة عجز الأدبيات التقليدية للتنمية السياسية من أن تتجاوز النزعة الإيديولوجية الكامنة فيها؛ حيث لم يخرج المنظور التحديثي ولا التنموي من بعده عن كونه مقاربة إنتشارية تهدف إلى رسم مسار خطي لتحوَل الدول الجديدة نحو التحديث السياسي وما ينجرَ عنه من "غربنة" "westernization" لتلك المنظومات السياسية؛ وبالرغم من أهمية دراسات"التغير السياسي"إلا أنَ هيمنة علم السياسة الغربي على حقل التنمية السياسية حال دون إعطائها أي أهمية تذكر في دراسات التنمية السياسية اللاحقة. Abstract: This study discusses the inability of the traditional literature for political development to transcend ideological tendencies; the modernist and developmental perspective has not emerged from it as an approach aimed at drawing a linear path for the transformation of the new states towards political modernization and the resulting "Westernization", Despite the importance of the studies of "political change"; the dominance of Western political science in the field of political development has prevented it from giving any importance in subsequent political development studies. key words: Political modernization; Political development; Political change; Developing countries; Western civilization
Keywords: التحديث السياسي ؛ التنمية السياسية؛ التغير السياسي؛ الدول النامية؛ الحضارة الغربية